2021
DOI: 10.1016/j.idcr.2021.e01226
|View full text |Cite
|
Sign up to set email alerts
|

Guillain-Barre syndrome 15 days after COVID-19 despite SARS-CoV-2 vaccination

Abstract: Guillain-Barre syndrome (GBS) following a SARS-CoV-2 vaccination has been repeatedly observed but GBS following a SARS-CoV-2 infection in a vaccinated patient has not been reported. A 69yo female developed paresthesias of both lower and upper limbs which were followed by progressive muscle weakness. The history was positive for a mild SARS-CoV-2 infection 15 days earlier. COVID-19 occurred despite a first dose of a vector-based SARS-CoV-2 vaccine, 40 days prior to onset of GBS. Since CSF investigati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 5 publications
0
4
0
Order By: Relevance
“…1-One patient had symptoms of GBS 40 days after receiving the first AstraZeneca dose, yet he had covid infection 15 days before symptoms’ onset and thus was excluded from our literature review ( Finsterer, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…1-One patient had symptoms of GBS 40 days after receiving the first AstraZeneca dose, yet he had covid infection 15 days before symptoms’ onset and thus was excluded from our literature review ( Finsterer, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…According to published data, the most CNS complications to SARS-CoV-2 vaccination include sinus venous thrombosis, headache (6-7), acute disseminated encephalomyelitis (ADEM) (8), acute encephalitis (9), and transverse myelitis (10). PNS complications following SARS-CoV-2 vaccinations include Guillain-Barre syndrome (GBS) (11). Cardiac complications of SARS-CoV-2 vaccinations include acute myocardial damage, myocarditis or perimyocarditis (12,13).…”
Section: Discussionmentioning
confidence: 99%
“…As a result, there is a chance that we will miss out on new upcoming studies. Another limitation is that the patient in study number 11 had GBS after taking the vaccine and catching COVID‐19 despite being vaccinated, and we included this study as GBS cause is unclear and not confirmed regarding COVID‐19 disease or vaccination 27 . Finally, The last included study reported by FDA was not included in the meta‐analysis because of the lack of information about 100 patients who were reported to have GBS after the COVID‐19 vaccine because there is a disproportionate number of atypical cases of GBS 31…”
Section: Limitationsmentioning
confidence: 99%